Positron annihilation lifetime spectroscopy insight on free volume conversion of nanostructured MgAl2 O4 ceramics - Klym, Halyna; Karbovnyk, Ivan; Piskunov, Sergei; Popov, Anatoli I. (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Herein we demonstrate the specifics of using the positron annihilation lifetime spectroscopy (PALS) method for the study of free volume changes in functional ceramic materials. Choosing technological modification of nanostructured MgAl2 O4 spinel as an example, we show that for ceramics with well-developed porosity positron annihilation is revealed through two channels: positron trapping channel and ortho-positronium decay. Positron trapping in free-volume defects is described by the second component of spectra and ortho-positronium decay process by single or multiple components, depending on how well porosity is developed and on the experimental configuration. When using proposed positron annihilation lifetime spectroscopy approaches, three components are the most suitable fit in the case of MgAl2 O4 ceramics. In the analysis of the second component, it is shown that technological modification (increasing sintering temperature) leads to volume shrinking and decreases the number of defect-related voids. This process is also accompanied by the decrease of the size of nanopores (described by the third component), while the overall number of nanopores is not affected. The approach to the analysis of positron annihilation lifetime spectra presented here can be applied to a wide range of functional nanomaterials with pronounced porosity. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Published under the CC BY 4.0 license.
H.K. and A.I.P. are grateful for the support from the COST Action CA17126. H.K. was also supported by the Ministry of Education and Science of Ukraine (project for young researchers No. 0119U100435). In addition, I.K. and H.K. were also supported by the National Research Foundation of Ukraine via project 2020.02/0217, while the research of A.I.P. was funded by the Latvian research council via the Latvian National Research Program under the topic ?High-Energy Physics and Accelerator Technologies?, Agreement No: VPP-IZM-CERN-2020/1-0002. In addition, the research of A.I.P. has been supported by the Latvian-Ukrainian Grant LV-UA/2021/5. The Institute of Solid State Physics, University of Latvia (Latvia) as the Centre of Excellence has received funding from the European Union?s Horizon 2020 Framework Programme H2020-WIDESPREAD01-2016-2017- Teaming Phase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; Free-volume defects; Nanopores; Nanostructured ceramics; Positron annihilation; Positron trapping; Positronium decay